Criminal Responsibility for Theft of Personal Data by Bank Employees and Misuse of Identity by Merchants Providing BRI EDC Cash Swipe Services - Subroto, Bartholomews Kislew; Latumahina, Rosalinda Elsina (Universitas PGRI Madiun, 2025)
The purpose of this study is Cash swipe transactions or commonly called Gestun, or the scientific term is called (Cash Withdrawal) to be a solution for credit card customers who want to make cash withdrawals but not through ATMs. Card customers simply visit shops that have credit card swipe machines (EDC), then withdraw cash according to the desired amount. By doing Gestun, credit card customers seem to be shopping for goods through the shop, but what is obtained is not goods but money. So customers do not take goods but take cash in the amount of the desired withdrawal or the value of the price of the goods. Credit cards are often the target of crime because of the benefits in their use; especially with made-up pretexts are the most common crimes because people often use credit cards for purchases and down payments based on credit facilities. Credit card fraud is usually called credit card misuse and can be classified into various categories: issuing credit cards through credit card companies, using credit cards at franchise stores and banks, and others. Credit card misuse due to the application of open laws to be disputed in accordance with various uses of credit cards Cash swipe is one form of credit card misuse. The purpose of writing this law is to find out the regulation and supervision of cash swipes in Indonesia and to find out how the responsibilities of the parties that facilitate cash swipes, especially for Acquirers and Merchants in Indonesia